2007
DOI: 10.1183/09031936.00028507
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative scoring of an interferon-γ assay for differentiating active from latent tuberculosis

Abstract: The aim of this study was to assess the contribution of an interferon-c release assay (T-SPOT.TB) to the differentiation of active tuberculosis (TB) from latent TB infection by quantifying spot-forming units (sfu).The investigation was a prospective study of contacts exposed to a case of contagious TB and cases of HIV-negative culture-proven TB referred over a 16-month period. Tuberculin skin tests (TSTs) and T-SPOT.TB were performed in 310 contacts 8-12 weeks after exposure. In subjects with culture-proven TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 17 publications
1
63
1
8
Order By: Relevance
“…We used ROC curves to evaluate the T-SPOT.TB test, and they showed that the AUC for the T-SPOT.TB test, ESAT-6, and CFP-10 were 0.93, 0.91, and 0.9, respectively, which was higher than those described by Janssens et al and Ling et al (6,10). Our results suggest that the T-SPOT.TB test is a fast and accurate method for the diagnosis of ATB in China.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…We used ROC curves to evaluate the T-SPOT.TB test, and they showed that the AUC for the T-SPOT.TB test, ESAT-6, and CFP-10 were 0.93, 0.91, and 0.9, respectively, which was higher than those described by Janssens et al and Ling et al (6,10). Our results suggest that the T-SPOT.TB test is a fast and accurate method for the diagnosis of ATB in China.…”
Section: Discussioncontrasting
confidence: 41%
“…It is thought that there is an association between the activity of mycobacteria and the level of interferon gamma secretion and that the interferon gamma level in ATB is significantly higher than that in LTBI. Some authors have suggested that IGRAs have a role in the diagnosis of ATB (4, 5, 9), whereas others object to their use in ATB due to the low specificity (6,10,11). Currently, there are two commercially available IGRAs: QFT-G-IT and T-SPOT.TB.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with experimentally infected animals support this possibility (5). Indeed, many studies conducted with IGRAs have shown higher IFN-␥ responses in active TB patients than in LTBI cases (17,73,74,164). Discordant results, however, have also been obtained (113).…”
Section: Cellular Immune Responses and Infection Statementioning
confidence: 68%
“…Existing blood-based tests, such as IFN-γ release assays (IGRAs), measure IFN-γ + production in response to stimulation with Mtb-specific antigens ESAT6 and CFP10 and are specific for Mtb infection (3,4). However, IGRAs (e.g., QuantiFERON or T-SPOT.TB) fail to discriminate between ATB and latent Mtb infection (LTBI) (5,6) and are inadequate for monitoring treatment response (7). Since CD4 + T cells are the predominant cell type producing IFN-γ in response to Mtb infection (8), we hypothesized that host immune markers on Mtb-specific CD4 + T cells that correlate with pathogen load could confer discriminatory capacity to IFN-γ-based assays.…”
Section: Introductionmentioning
confidence: 99%